Creation of a Mentoring Program for Improving the Education of Industrial Engineers - Almeida, M. G. D. [UNESP]; Salgado, A. M. P. [UNESP]; Baronto, G. N. D.; IEEE (Ieee, 2015)
This document aims to present the creation of a mentoring program to be applied in developing industrial engineers students, while interns at the companies, into future junior industrial engineers. Its objective is to contribute to a better professional performance as engineers. It is a case-study for the RIP region (including the cities of Resende, Itatiaia and Porto Real), which is located in an industrial area in Rio de Janeiro State, in Brazil, better preparing the new junior engineers for the labor market. This study is still under development. The PDCA cycle was used as a base method to create the program, since this was developed in 4 semesters at the university. As a draft result, which needs to be confirmed, 87% of mentors and mentees approved the program as efficient, based on initial targets.
Keywords: Mentoring program; student professional development; young engineers' education